Gordeev O.A, Karmalita A.K. Analysis of geometrical parameters and picture profile mastyloutrymuvalnoho of the fluid in a spherical hole on sliding surface. - Гордєєв, О.А.; Кармаліта, А.К. (Problems of Tribology, 2014)
Much of the cost of maintenance and repair of equipment of light industry, such as a variety of high-speed sewing machines due to the wear of friction units. At a time when starting and stopping is the most exposed areas. An analytical model of the movement of oil in a spherical hole.The movement of oil in a spherical hole in the neck of the shaft in the bearing sliding represented as a problem of plane motion of a viscous fluid between non-parallel planes. The influence of geometrical parameters mastyloutrymuvalnoho profile to a depth nesuschoho lubricant layer. As a result of research settings adjusted return appearance of the fluid in the hole and shows emergence of circular motion in mastyloutrymuvalnomu liquid layer, indicating that the maintenance of oil in the hole. Dependences of the depth nesuschoho layer of hole sizes showed a significant effect on the lubricating layer and a lower impact on the depth of his hole .